ASSESSMENT OF GLOBAL RISKS FROM THE POSITION OF SECURITY MANAGEMENT OF UKRAINIAN ENTERPRISES - CHMUTOVA, Iryna; HAINALII, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study aims to evaluate the global risks affecting Ukrainian enterprises, focusing on their probability of occurrence and the potential strength of their impact, particularly from the perspective of security management. The main objective is to identify the most pressing threats to business activities in Ukraine and develop effective strategies to mitigate these risks. Drawing upon the reports of the World Economic Forum (2018-2024), the research investigates several key global risks, including economic, environmental, technological, and social threats, that have reshaped enterprise security priorities in the country. Notably, the study emphasizes the growing concerns regarding climate change, cyber threats, pandemics, and geopolitical instability. The paper also includes the results of a survey conducted among 49 Ukrainian enterprises, which assessed the likelihood and impact of various global risks such as economic recession, inflation, forced migration, cybersecurity breaches, and interstate conflicts. The risks were evaluated using a five-point Likert scale, which facilitated an understanding of their relative significance. The findings indicate that the most likely and influential risks for Ukrainian enterprises are those related to economic crises, inflation, forced migration, and cyber threats. Based on these findings, the study recommends strengthening cybersecurity frameworks, adapting supply chain management strategies, and accounting for environmental and financial variables in risk management approaches. A risk management matrix derived from the survey data provides a practical tool for enterprises to prioritize resource allocation and focus on key security measures. Furthermore, the research underscores the importance of assessing various components of enterprise security, such as intellectual, personnel, political, legal, innovative, environmental, and financial security. This holistic approach ensures that enterprises are better equipped to manage strategic risks and maintain operational resilience amidst the ongoing global challenges. By adopting these strategies, Ukrainian enterprises can enhance their ability to navigate uncertain and rapidly changing risk landscapes.